Incidence of Abruption and Placenta Previa in Pregnant with Previous Caesarian Section - Baidaa Abdulkareem Alwan; Areej Sabah abdulridha (Institute of Medico-legal Publications Pvt Ltd, 2022)
Caesarean section is a surgical procedure in which the incision made through a women’s abdomen(laparotomy) and uterus (hysterectomy) to deliver one or more babies. In each previous c/s the risk ofplacenta previa and abruption increase. The aim of this study is to find out the associated between theprevious caesarean section and placenta previa and abruption in this pregnancy. A retrospective studywas carried out during the period between 1st July 2018 and 20th august 2019 in Al-Zahraa TeachingHospital. During the period of study, 119 pregnant women with history of previous scar presented to thehospital for vaginal delivery or c/s, 70 of these patients diagnosed that they have placenta previa and ashave placenta abruption by ultrasound and confirmed during delivery. Another 49 patients were withoutcomplication. Pregnant women with APH due to other causes were excluded. Data were collectedthrough detailed history. Official agreements and verbal consent of all women were taken. Statisticalanalysis performed by using the statistical package for social sciences and appropriate statistical testwere applied.